Volumetric Assessment of Root Canal Obturation Using 3% Nano-Chitosan versus Zinc Oxide Eugenol (ZOE) and Iodoform-Calcium Hydroxide (Metapex), in Primary Root Canals Shaped with Rotary versus Manual Methods: A Preliminary In-Vitro Spiral CT Study - Elahe Babashahi; Maryam Mohmadi Kartalaie; Leila Basir; Vahid Rakhshan (Tehran University of Medical Sciences, 2019)
Objectives: In this study, chitosan was introduced and used as a substitute for pulpectomy obturation against conventional materials: zinc oxide eugenol (ZOE) and iodoform-calcium hydroxide (Ca(OH)2) compounds. Also, efficacies of rotary versus manual instrumentations were compared. Materials and Methods: This preliminary in-vitro study was performed on 152 intact non-resorbed root canals of primary molars divided into rotary (n=78) versus hand-instrumentation (n=74) and also into ZOE (n=53), iodoform-Ca(OH)2 (n=50), and 3% nano-chitosan (n=49). Canals were cleaned/shaped using hand or rotary files. Canal spaces were measured using spiral computed tomography (CT). Canals were then obturated using the three materials. The percentages of obturation volume (POV) were estimated. Rotary and manual instrumentations were compared in terms of canal spaces before and after obturation. Three obturation materials were compared in terms of canal spaces after obturation (α=0.05). Results: Average POVs of materials were 96.54% (ZOE), 97.87% (Metapex), and 74.74% (nano-chitosan; P=0.000). POV of chitosan differed from the other two (P=0.000) but the other two were similar (P=0.896). Average POVs were 91.46% (manual) and 88.51% (rotary); the difference was not significant (P=0.322). Pre-obturation spaces of canals for different methods were 3.89 mm3 (manual) and 3.26 mm3 (rotary); the difference was significant (P=0.013). Two-way ANCOVA showed a significant effect of materials (P=0.000) but not root length (P=0.585) or shaping methods (P=0.362) on POVs. Conclusions: Nano-chitosan showed a considerable success rate but it still needs reformulation as it was weaker than the extremely successful commercial competitors.....